Lactate ≥2 mmol/L plus qSOFA improves utility over qSOFA alone in emergency department patients presenting with suspected sepsis. (26th November 2017) - Shetty, Amith; MacDonald, Stephen PJ; Williams, Julian M; van Bockxmeer, John; de Groot, Bas; Esteve Cuevas, Laura M; Ansems, Annemieke; Green, Malcolm; Thompson, Kelly; Lander, Harvey; Greenslade, Jaimi; Finfer, Simon; et al.
Abstract: Objective: The Sepsis‐3 task force recommends the use of the quick Sequential Organ Failure Assessment (qSOFA) score to identify risk for adverse outcomes in patients presenting with suspected infection. Lactate has been shown to predict adverse outcomes in patients with suspected infection. The aim of the study is to investigate the utility of a post hoc lactate threshold (≥2 mmol/L) added qSOFA score (LqSOFA(2) score) to predict primary composite adverse outcomes (mortality and/or ICU stay ≥72 h) in patients presenting to ED with suspected sepsis. Methods: Retrospective cohort study was conducted on a merged dataset of suspected or proven sepsis patients presenting to ED across multiple sites in Australia and The Netherlands. Patients are identified as candidates for quality improvement initiatives or research studies at respective sites based on local screening procedures. Data‐sharing was performed across sites of demographics, qSOFA, SOFA, lactate thresholds and outcome data for included patients. LqSOFA(2) scores were calculated by adding an extra point to qSOFA score in patients who met lactate thresholds of ≥2 mmol/L. Results: In a merged dataset of 12 555 patients where a full qSOFA score and outcome data were available, LqSOFA(2) ≥2 identified more patients with an adverse outcome (sensitivity 65.5%, 95% confidence interval 62.6–68.4) than qSOFA ≥2 (sensitivity 47.6%, 95% confidence interval 44.6– 50.6). The post hoc addition of lactate threshold identified higher proportion of patients at risk of adverse outcomes. Conclusions: The lactate ≥2 mmol/L threshold‐based LqSOFA(2) score performs better than qSOFA alone in identifying risk of adverse outcomes in ED patients with suspected sepsis.